Effective Management Tool for Civil Construction Works: Trends and megatrends in Building Information Modeling (BIM) methodology (Research, Society and Development, 2025)
The existence of an increasingly dense and competitive market in Civil Construction is considered, with a scenario that has been providing the feasibility of consolidating the challenges imposed by clients while increasingly consolidating the use of technology in the sector. New methods have been emerging in addition to the adoption of new materials and machines in conjunction with the adoption of virtual simulations that end up providing a better presentation of projects for clients, providing efficiency, effectiveness and quality, with lower costs and deadlines and this has been consolidated in an integrated manner with the Modeling or Building Information Models (BIM) methodology. Thus, this research has as its general objective the registration of the use of BIM in small and large projects with evidence of its advantages and disadvantages, and, as specific objectives, the explanation of the BIM concept; the analysis of BIM software (Revit®); and comparison with the predecessor method Computer Aided Design (CAD). To consolidate these objectives, a literature review of a documentary and historical nature based on published materials on the subject was adopted as the research methodology, with an approach to the main terms and definitions used in the area and related topics. Finally, the study concludes by highlighting the opportunities with the use of BIM and its processes, in addition to recording the reduction of risks and errors in construction with the increase in the competitive edge in the preparation of projects and the minimization of time associated with the maximization of profits for its users.